The U.S. Army in Southeast Asia - Chalk, Peter (RAND Corporation, 2023)
This RAND report examines the U.S. Army role in Southeast Asia. Under current benign conditions, efforts should focus on supporting defense reform, addressing transnational threats, and balancing China. If the outlook deteriorates, the United States should increase security cooperation, conclude new regional basing agreements, expand disaster assistance, and create policies to encourage risk-averse Chinese behavior.